2022
DOI: 10.3390/ijerph191711046
|View full text |Cite
|
Sign up to set email alerts
|

Change in Factors Affecting Cyberbullying of Korean Elementary School Students during the COVID-19 Pandemic

Abstract: The importance of social networking and the online environment as core factors in building relationships has grown as a result of the COVID-19 pandemic, which limited in-person activities. As classes transitioned to online platforms, there was an influx of elementary school students into the cyberspace, increasing the risk of exposure to cyberbullying. This study analyzed the factors influencing the experience of cyberbullying among Korean elementary school students around 2020, when the spread of COVID-19 beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 33 publications
1
19
1
1
Order By: Relevance
“…Finally, the findings of this study back up prior studies [10,54,96,110], suggesting that cyberbullying, cyber harassment, and cyberstalking have ethical ramifications that impact cyber behavior. As a result, web-based communication and relationships should be complex.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Finally, the findings of this study back up prior studies [10,54,96,110], suggesting that cyberbullying, cyber harassment, and cyberstalking have ethical ramifications that impact cyber behavior. As a result, web-based communication and relationships should be complex.…”
Section: Discussionsupporting
confidence: 74%
“…Law enforcement officers should be alert, proactive, and inventive in their responses to these offenses. Cyberbullies, unlike traditional bullies, may conceal their identities [54]. Traditional bullying is still more common than internet bullying, according to a meta-analytical study based on 80 past studies [55], which may explain why cyberbullying is considered a sub-category of bullying in general [56].…”
Section: Cyber Bullying (Cb)mentioning
confidence: 99%
“…Kasus cyberbullying sangat sulit untuk dikendalikan karena pelakunya tidak terlihat, selain itu orang tua serta guru sering kali menganggap perilaku bullying merupakan hal sepele dan mengganggap anak tidak mungkin menjadi pelaku atau bahkan korban dari cyberbullying, hal ini disebabkan karena cyberbullying dilakukan melalui media sosial bukan secara langsung, bahkan terkadang untuk melakukan cyberbullying ini melaku menggunakan akun samara (Aizenkot, 2021a;Choi, 2022;Daulay, 2022;DePaolis, 2019;Doumas, 2021;Park, 2021;Touloupis, 2022aTouloupis, , 2022bZhang, 2021). Perilaku cyberbullying bisa merugikan siswa yang bersangkutan ataupun orang-orang yang berada disekitarnya, kemudian jika hal ini dibiarkan berlarut-larut tanpa adanya upaya penanganan dari pihak sekolah pada akhirnya dapat menjadi contoh bagi siswa yang lain untuk melakukan hal yang sama dan menimbulkan citra yang kurang positif terhadap pelajar dan dunia pendidikan pada umumnya.…”
Section: Pendahuluanunclassified
“…Researchers in [49] reviewed recently published studies and identified a positive trend in utilizing the metaverse for distance learning and post-pandemic education. However, authors in [15] also cautioned against the potential risks of cyberbullying in virtual societies within the metaverse.…”
Section: Future Directions In Educational Technologymentioning
confidence: 99%